STRATEGI PELAYANAN BIRO ADMINISTRASI AKADEMIK MAHASISWA UNIVERSITAS DIAN NUSWANTORO - Agung Sedayu; Ngatindriatun Ngatindriatun (MEDIA, 2012)
This study discusses how the Performance of academic administration bureau (BIAK) at the University of Dian Nuswantoro, how the characteristics, expectations, performance and level of student satisfaction with the services provided by the academic administration bureau (BIAK) at the University of Dian Nuswantoro and how big the influence of the service provided by academic administration bureau (BIAK) on the student satisfaction levels. Sampling use purposive sampling technique with a number of samples taken as many as 100 student respondents. To analyze the data the researcher uses multiple linear regression equation model to determine the factors that affect students satisfaction on quality service of Academic Administration Bureau (BIAK) Dian Nuswantoro University. Based on the results of research conducted can be concluded that the quality of service of the academic administration bureau (BIAK) simultaneously affect student satisfaction. This means Tangible, Reliability, Responsiveness, Assurance, Empathy of academic administration bureau (BIAK) simultaneously affect student satisfaction. Where the service quality variables affect satisfaction by 84.8%. So that the academic administration bureau (BIAK) Dian Nuswantoro University must keep the quality of services that are included in the category of very high.